Economic evaluation of the prevention of falls resulting from missed care in polish hospitals - Wieczorek-Wójcik, Beata; Gaworska-Krzemińska, Aleksandra; Owczarek, Aleksander Jerzy; Kilańska, Dorota (Frontiers in Public Health, 2024)
Objectives Falls are associated with increased morbidity, mortality, prolonged hospitalization and an increase in the cost of treatment in hospitals. They contribute to the deterioration of fitness and quality of life, especially among older patients, thus posing a serious social and economic problem. They increase the risk of premature death. Falls are adverse, costly, and potentially preventable. The aim of the study was to analyze the cost-effectiveness of avoiding one fall by nurse care provided by the nurses with higher education, from the perspective of the health service provider. Methods The economic analysis included and compared only the cost of nurse intervention measured by the hours of care provided with higher education in non-surgical departments (40.5%) with higher time spend by nurses with higher education level an increase in the number of hours by 10% (50.5%) to avoid one fall. The time horizon for the study is 1 year (2021). Cost-effectiveness and Cost–benefit analysis were performed. All registered falls of all hospitalized patients were included in the study. Results In the analyzed was based on the case control study where, 7,305 patients were hospitalized, which amounted to 41,762 patient care days. Care was provided by 100 nurses, including 40 nurses with bachelor’s degrees and nurses with Master of Science in Nursing. Increasing the hours number of high-educated nurses care by 10% in non-surgical departments decreased the chance for falls by 9%; however, this dependence was statistically insignificant (OR = 1.09; 95% CI: 0.72–1.65; p = 0.65). After the intervention (a 10% increase in Bachelor’s Degrees/Master of Science in Nursing hours), the number of additional Bachelor’s Degrees/Master of Science hours was 6100.5, and the cost was USD 7630.4. The intervention eliminated four falls. The cost of preventing one fall is CER = USD 1697.1. Conclusion The results of these studies broaden the understanding of the relationship among nursing education, falls, and the economic outcomes of hospital care. According to the authors, the proposed intervention has an economic justification.